Triplets - (:unkn) unknown (Coy C. Carpenter Library, 1957)
Published in Charity and Children newspaper, vol. 70, no. 1, May 2, 1957, p.1
The triplets shown here are (L-R) Jimmy Dean, Jackie Lane, and Johnny Wayne, sons of Mr. and Mrs. James Otis Fulp of Danbury, North Carolina. They were born at another hospital in 1957 but came to North Carolina Baptist Hospital for specialized care. The premature nursery at NCBH was one of the few of its kind in the state during this time. In the 1950s, the nursery averaged 11 babies at one time and the length of stay was usually six weeks.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth